Melatonin Mediates Axillary Bud Outgrowth by Improving Nitrogen Assimilation and Transport in Rice - Yang, Guo; Wei, Xilin; Fang, Zhongming (Frontiers in Plant Science, 2022)
Melatonin plays an important role in plant resistance to biotic and abiotic stresses. However, whether melatonin is involved in the regulation of plant architecture, such as the formation of axillary bud outgrowth or tillering, in rice remains unknown. Here, we found that different concentrations of melatonin influenced axillary bud outgrowth in rice, and moderate melatonin concentrations also alleviated the inhibition of axillary bud outgrowth in the presence of high concentrations of basic amino acids lysine and arginine. Furthermore, transcriptome analysis demonstrated that genes involved in nitrogen metabolism and phytohormone signal transduction pathways may affect axillary bud outgrowth, which is regulated by melatonin. We determined that the differentially expressed genes glutamine synthetase OsGS2 and amino acid transporter OsAAP14, which are involved in nitrogen metabolism and are regulated by melatonin and basic amino acids, were the key regulators of axillary bud outgrowth in rice. In addition, we validated the functions of OsGS2 and OsAAP14 using rice transgenic plants with altered axillary bud outgrowth and tillers. Taken together, these results suggest that melatonin mediates axillary bud outgrowth by improving nitrogen assimilation and transport in rice.